Self emulsifying Liquisolid tablets for enhanced oral bioavailability of repaglinide: In vitro and in vivo evaluation - Gamal M El Maghraby, Mohamed A Osman, Houyda E Abd-Elrahman, Alaa E. Elsisi (Journal of Applied Pharmaceutical Science, 2014)
The aim of this work was to enhance dissolution rate and oral bioavailability of repaglinide. This was achieved by development of liquisolid tablet with the liquid component being self emulsifying drug delivery system (SEDDS). Thus SEDDS was prepared using oleic acid as oil and Tween 20 or its mixture with propylene glycol surfactant/cosurfactant system. Formulations containing different oil concentrations were loaded with various amounts of drug and subjected to in vitro evaluation. Optimum formulations were prepared and evaluated as liquisoild tablets. This involved administration to diabetic rats and monitoring blood glucose level. Incorporation of repaglinide in the SEDDS enhanced the dissolution rate of the drug irrespective to the fraction of molecularly dispersed drug, compared to unprocessed drug. Formulation of the optimum system as liquisolid tablet did not change the dissolution pattern of the SEDDS indicating that the drug exists in solution or partially dissolved form. The in vivo study revealed enhancement of the rate and extent of drug absorption after incorporation into the SEDDS, this was evidenced by the rapid onset of action and higher area above the blood glucose versus time curve compared to the unprocessed drug. Overall, the developed system was able to increase the bioavailability of repaglinide.
Keywords: Repaglinide bioavailability, nanoemulsion, diabetes, blood glucose, repaglinide metabolism.